Zirconium and hafnium complexes with new tetra-azane ligands: Synthesis, characterization and catalytic properties for ethylene polymerization. (14th December 2015) - Ji, Xiangdong; Luo, Xuyang; Gao, Wei; Mu, Ying
Graphical abstract: Zirconium and hafnium complexes bearing new tetra-azane ligands, {1, 2-[(2′-(ArN)C6 H4 HCN)]2 C6 H4 }MCl2, were synthesized in high yields and studied as ethylene polymerization catalysts to form ultra-high molecular weight polyethylene. Abstract: Two new anilido-imine tetra-azane ligands, 1, 2-[(2′-(ArNH)C6 H4 HCN)]2 C6 H4 (Ar = 2, 6-Me2 C6 H3 (L 1 H2 ) and 2, 6- i Pr2 C6 H3 (L 2 H2 )), were synthesized by the condensation reaction of o -phenylenediamine with the corresponding 2-(arylamino)benzaldehyde, and their zirconium and hafnium complexes, L 1 MCl2 (M = Zr (1b ), Hf (1c )) andL 2 MCl2 (M = Zr (2b ), Hf (2c )), were synthesized in high yields (61–66%) by the reactions ofL 1 Li2 andL 2 Li2 with MCl4 in toluene. Direct HCl-elimination reactions ofL 1 H2 with MCl4 (M = Ti, Zr, Hf) in toluene at 140 °C under vacuum afforded the productsL 1 HMCl3 [M = Ti (1a ′), Zr (1b ′), Hf (1c ′)] with a partially deprotonated tridentate ligand in good to high yields (48–70%). All the new complexes were characterized by 1 H and 13 C NMR spectroscopy and the molecular structures of1b and2c were determined by single crystal X-ray diffraction analysis. The metal centers in both complexes are six-coordinated with a distorted octahedral geometry. Upon activation with MAO or AlR3 /Ph3 CB(C6 F5 )4, complexes1b –1c and2b –2c all exhibit moderate catalytic activity for ethylene polymerization and produce linear polyethylene with ultra-high molar masses (100–184 × 10 4  g/mol).